REGENERATION OF THE PULP-DENTIN COMPLEX - Gomes Filho, João Eduardo [UNESP]; Duarte, Paulo C. T. [UNESP]; Lodi, Carolina S. [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2020)
Complete restoration of a functional pulp-dentin complex cannot be achieved by conventional endodontic treatment. However, with the advent of regenerative medicine, it became possible to regenerate pulp and dentin through alternative endodontic regenerative procedures. These procedures are based on the principles of tissue engineering that aim to develop new tissues to replace lost or malfunctioning organs using a source of stem cells, a three-dimensional scaffold for the growth of these cells, and signaling molecules. The most common endodontic regenerative procedure uses blood clots and cell transplantation enriched with or without platelet-rich plasma or stem cell enrichment. Revascularization in humans by using blood clot has been reported in several papers but pulp regeneration has been achieved only in dogs, using stem cell transplantation. The clinician performs blood clot technique relatively easily. However, cell cultivation and expansion have been linked to reduced viability, selection, and undesirable reprogramming and/or cellular dedifferentiation. In addition, it is expensive, time-consuming, and associated with an increased risk of infection. Moreover, as the pulp diminishes with age, alternative sources of stem cells, such as bone marrow, apical papilla, deciduous teeth, periodontal ligament, and adipose tissue need to be evaluated. The aim of this chapter is to highlight the tissue engineering principles relevant to the pulp-dentin complex regeneration using stem cell transplantation and/or blood clot strategies.
Keywords: pulp biology; pulp-dentin complex; regeneration